Characterization of phosphorylation changes and protein kinase activities in wheat head following infection with the fungal pathogen Fusarium graminearum - Bordeleau, Christian (University of Ottawa (Canada), 2003)
The presence on wheat crops of the fungal pathogen Fusarium graminearum poses serious financial and health-related problems in Canada. The fungus causes a significant decrease in yield and quality of the crop, in addition to producing mycotoxins, which can survive the milling process. Signaling processes involving protein kinases are thought to play a major role in the activation of a host defense response. A research project employing western detection experiments and kinase assays was initiated to determine whether the presence of F. graminearum caused changes in the level of protein kinases in cultivars Frontana (resistant) and Roblin (susceptible). The results indicated that F. graminearum had modest effects on phosphorylation levels of threonine and tyrosine residues. Moreover, differences occurred between the resistant and susceptible cultivar. Kinase assays did not show any variation in activity in either cultivar. A MAPK (w&barbelow;heat M&barbelow;APK h&barbelow;omologue-1&barbelow;) homologue was cloned, sequenced and shown to be identical to the wck-1 sequence found in the public database. Preliminary results show an increase in the level of transcript in the Fusarium-treated Frontana sample. The implications of the results are discussed.
Keywords: Biology, Ecology.; Agriculture, Plant Pathology.